An Analysis of Coexistence of Multiple Oral Parafunctional Habits in Extraverts - Sarah Ali Chaudhry, Rizwana Sultan, Amina Nawaz, Asma Shakoor, Zara Mehboob, Hira Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the presence and coexistence of multiple oral parafunctional habits in individuals with extravert personality type Methodology: A Cross-sectional descriptive study was conducted at the College of Dentistry, Sharif Medical and Dental College, Lahore, over 5 months, from July to November 2021. Data was collected using medical questionnaire and ten item personality inventory scale (TIPI). Results: There was significant association in the coexistence of parafunctional habit of nail biting with tooth clenching (p≤0.001), tooth grinding(p≤0.001), biting hard objects (p≤0.001) and chewing gum (p=0.027). Practical Implication: This study will help dental practitioners use personality assessment as an effective and important tool to find the propensity of an individual for development of oral parafunctional habits. In this way they will be able to provide timely treatment and counselling to the individuals before their dental health deteriorates due the development of oral parafunctional habits. Conclusion: The oral parafunctional habits found to coexist the most with nail biting habit was tooth grinding followed by biting hard objects, chewing gum and tooth clenching. Keywords: Extraverts, Oral parafunctional habits, Ten Item Inventory Scale, Nail Biting